STRENGTHENING ARTIFICIAL INTELLIGENCE (AI) IN THE ESTABLISHMENT OF E-GOVERNMENT IN VIETNAM IN THE CURRENT PERIOD - Thuy, Nguyen Xuan; Văn, Nguyen Xuan; Hoa, Tran Thi; Huong, Ta Thi Thanh (International Journal of Psychosocial Rehabilitation, 2020)
In the current period, the construction of e-government in Vietnam is being carried out in a strong, comprehensive and initially obtained favorable and positive results. In order to build and perfect e government as required by the 4.0 era, it is necessary to strengthen and promote the application of artificial intelligence. The article contributes to clarifying the situation and providing solutions to promote the application of artificial intelligence in the construction of e-government in Vietnam in the coming time.